MODERN ELECTRONIC SERVICES OF THE LIBRARY TO SUPPORT EDUCATIONAL AND SCIENTIFIC - SOKIL, Mariia; ZVORSKYI, Andrii (Herald of Khmelnytskyi National University. Technical sciences, 2023)
University libraries have undergone significant changes in recent years, with the advent of new technologies and the increased use of electronic services. These services have revolutionized the way libraries support educational and scientific processes in universities. One of the most important electronic services offered by modern libraries is online access to a wide range of academic journals, books, and other scholarly materials. This allows students and faculty members to access the latest research and information in their fields, regardless of their physical location.Another important electronic service is the use of digital databases, which allow users to search for and access a wide range of information on a variety of topics. These databases can be used for research, writing papers, and other academic projects.In addition to providing access to electronic resources, libraries also offer a wide range of services to support the use of these resources. For example, many libraries have reference librarians who can help users navigate the digital resources and find the information they need. Libraries play an essential role in supporting educational and scientific processes in universities by providing access to a wide range of electronic resources and services. These resources and services include online access to academic journals and books, digital databases, reference assistance. With the evolution of technology, libraries are also adapting and providing services such as e-books, digital library cards, and online library account management. In this article we describe and analyze new digital services which was implemented in Scientific Library of Lviv Polytechnic National University.
Keywords: Internet resources; information resources; popularization; electronic services; library resources